If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Lg(-4x + -30) = 2 Reorder the terms: gL(-30 + -4x) = 2 (-30 * gL + -4x * gL) = 2 (-30gL + -4gxL) = 2 Solving -30gL + -4gxL = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -2 + -30gL + -4gxL = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + -30gL + -4gxL = 0 Factor out the Greatest Common Factor (GCF), '-2'. -2(1 + 15gL + 2gxL) = 0 Ignore the factor -2.Subproblem 1
Set the factor '(1 + 15gL + 2gxL)' equal to zero and attempt to solve: Simplifying 1 + 15gL + 2gxL = 0 Solving 1 + 15gL + 2gxL = 0 Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 15gL + -1 + 2gxL = 0 + -1 Reorder the terms: 1 + -1 + 15gL + 2gxL = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 15gL + 2gxL = 0 + -1 15gL + 2gxL = 0 + -1 Combine like terms: 0 + -1 = -1 15gL + 2gxL = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x-6-6x=-9 | | -(-7x+5)+6(7-x)=43 | | 3x+4=3x+12 | | 1/4m=-2 | | -20-x=-(6x-2)+4x | | 1=k/-5-4 | | 17s+-14s+-5s=17 | | -6(-2b-2)-2(b+4)=34 | | X+2-4x=-22 | | 12j-15j-j=20 | | 4(-3b+5)=-28 | | 2+2x+7x=-7 | | 18h-16h=14 | | 5.25m=-42 | | x+24+8x-12+8x-12+x=360 | | -34=2(5k+8)+5(k+2) | | -2992+272m=0 | | -7x+5+5x=3 | | 5cos^2x-2sinx=2 | | 3-6=2x-3 | | n/2=-1/34 | | 4+4x+3x=-10 | | Y^2=16/64 | | -.8x=24 | | Q^2=225 | | |1/3d-6=15| | | -5x+1=-6x-6 | | 5(x+1)=63-2x-2x | | 50=6(n+8)-(8n-6) | | 1-x+7x=55 | | -7x+4+2x=39 | | -33=-3(r+5)-3(-6r+6) |